2006
DOI: 10.1111/j.1600-0722.2006.00402.x
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular jaw movement capacity in 10–17‐yr‐old children and adolescents: normative values and the influence of gender, age, and temporomandibular disorders

Abstract: The aims of this study were, first, to report normative values for jaw movements in Caucasian children and adolescents (maximum opening, laterotrusion, and protrusion) and, second, to investigate the influence of age, gender, and temporomandibular disorders (TMD) on jaw movement capacity. The population-based study included 1,011 randomly selected German children and adolescents, aged 10-17 yr. Case histories, as well as mandibular movements and the presence of TMD, were assessed according to the Research Diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
65
9
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 17 publications
15
65
9
8
Order By: Relevance
“…Unlike in our series, Masumi et al found no significant differences in terms of maximum aperture in the four groups of TMJD considered in their study (arthromyalgia, arthromyalgia with disc-condyle incoordination, isolated disc-condyle incoordination, and osteoarthrosis) -though the sample size involved (n = 41) could explain the absence of differences (16). In the case of lateralization movements, our results (mean = 6.2 mm for right lateralization and 6.5 mm for left lateralization) are clearly below the value considered by Hirsch et al (15) to represent the lower limit of normality (8 mm). In 1921, Wertheim observed that most individuals are able to move the mandible more towards the left side than to the right side.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Unlike in our series, Masumi et al found no significant differences in terms of maximum aperture in the four groups of TMJD considered in their study (arthromyalgia, arthromyalgia with disc-condyle incoordination, isolated disc-condyle incoordination, and osteoarthrosis) -though the sample size involved (n = 41) could explain the absence of differences (16). In the case of lateralization movements, our results (mean = 6.2 mm for right lateralization and 6.5 mm for left lateralization) are clearly below the value considered by Hirsch et al (15) to represent the lower limit of normality (8 mm). In 1921, Wertheim observed that most individuals are able to move the mandible more towards the left side than to the right side.…”
Section: Discussioncontrasting
confidence: 52%
“…However, Elfving et al recorded some type of joint sound in 36% of their controls (13); similar data had already been published by Gross et al in 1986 -with the documenting of joint sounds in 37% of the asymptomatic population (14). In our study, both the global mean maximum aperture and the mean value corresponding to each of the diagnostic groups were clearly smaller than the threshold considered by Hirsch et al to mark the normal limit: "The upper limit of the lowest decentile is 43 mm, and any lesser maximum aperture should be regarded as a limitation of the latter" (15). Unlike in our series, Masumi et al found no significant differences in terms of maximum aperture in the four groups of TMJD considered in their study (arthromyalgia, arthromyalgia with disc-condyle incoordination, isolated disc-condyle incoordination, and osteoarthrosis) -though the sample size involved (n = 41) could explain the absence of differences (16).…”
Section: Discussionmentioning
confidence: 47%
“…Unlike what was found in studies in children, researches show statistically significant differences between genders in populations comprised of adolescents 17 and adults 9 , revealing that sexual maturity, in which the differentiation of various physical characteristics of humans occurs, seems to be impactful, also, regarding the mandibular range of motion 10,16 .…”
Section: Thismentioning
confidence: 42%
“…The measures studied seem to follow the same tendency of other physical characteristics that start to differentiate according to gender at puberty since gender differences have been detected in samples of adolescents and adults (2,10,15,19,20).…”
Section: Discussionmentioning
confidence: 99%
“…There is a great demand for clinical speech therapy for children aged six to 12 years, but normal data regarding maximum mandibular opening, lateral excursion and protrusion in children are scarce both in the international (3,(8)(9)(10) and in the Brazilian (1,6,11) literature.…”
Section: Introductionmentioning
confidence: 99%